Preparation method for in-situ local regulation and control of cell morphology of polymer foam material and polymer foam material

By using a foaming method combining composite polymers with hydrophilic materials and additives, the cell morphology of polymer foam materials can be controlled, solving the problems of low preparation efficiency and high cost in existing technologies, and realizing the efficient preparation and performance improvement of lightweight micron-sized foam materials.

CN121159925APending Publication Date: 2025-12-19CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511304148.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-12
Publication Date
2025-12-19

AI Technical Summary

Technical Problem

Existing technologies struggle to efficiently and cost-effectively prepare polymer foam materials with both honeycomb and concave pore structures. Furthermore, the low efficiency and high cost of 3D and 4D printing technologies limit their application in fields requiring lightweight materials and high mechanical properties.

Method used

By combining polar and non-polar polymers, hydrophilic substances, and additives, a foaming precursor is formed. This precursor is then mixed with a foaming agent and water under specific temperature and pressure conditions to perform a foaming process, thereby controlling the cell morphology, including the formation of honeycomb and concave corner structures.

Benefits of technology

This technology enables the efficient and low-cost preparation of lightweight micron-sized polymer foam materials, improving the designability and usability of material properties and making them suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005593782530000011
    Figure HDA0005593782530000011
  • Figure HDA0005593782530000012
    Figure HDA0005593782530000012
  • Figure HDA0005593782530000013
    Figure HDA0005593782530000013
Patent Text Reader

Abstract

The invention provides a preparation method for in-situ local regulation and control of the cell morphology of a polymer foam material and the polymer foam material, and the preparation method comprises the following steps: compounding a polar polymer, a non-polar polymer, a hydrophilic substance and an auxiliary agent, and molding to obtain a foaming precursor; the hydrophilic substance accounts for 0-20wt% of the foaming precursor, and the auxiliary agent accounts for 0-20wt% of the foaming precursor; mixing the foaming precursor, a foaming agent and water, saturating for 30 minutes to 8 hours at the temperature of 60 to 200 DEG C and the pressure of 3 to 25 MPa, and foaming to obtain the polymer foam material. According to the method, the pore form can be locally regulated in situ in the polymer foam material preparation process, and the process is simple, green and environment-friendly; according to the method, the morphology and Poisson's ratio of the polymer foam material can be regulated and controlled, and the designability of the material performance can be improved, so that the usability of the polymer foam material is greatly improved, and the development of the field is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer foam material preparation technology, and particularly relates to a method for preparing polymer foam material with in-situ localized control of cell morphology and the polymer foam material itself. Background Technology

[0002] Polymer foams are widely used in various fields such as daily life, transportation, construction, aerospace, and military due to their excellent properties, including lightweight, shock absorption, high specific strength, good sound and heat insulation, good energy absorption, and ease of processing. Besides the properties of the polymer matrix itself, the structure and morphology of the cell structure also significantly influence their superior properties. Typically, polymer foams with a "honeycomb" cell morphology have a positive Poisson's ratio, and research on these positive Poisson's ratio foams is relatively mature. However, polymer foams with a "concave" cell structure have a negative Poisson's ratio. This unique cell morphology gives them not only the conventional properties of polymer foams but also superior properties such as high shear modulus, good fracture toughness, high yield strength, good notch resistance, good energy absorption, and good resilience. Therefore, negative Poisson's ratio polymer foams are gradually becoming a focus of research.

[0003] Currently, there are many methods for preparing positive and negative Poisson's ratio polymer foams. For example, positive Poisson's ratio polymer foams can be prepared using chemical foaming, physical foaming, mechanical foaming, template methods, and 3D and 4D printing technologies. Negative Poisson's ratio polymer foams can be prepared using triaxial compression-heating, vacuum-heating, high-pressure-heating, multiphase triaxial thermal compression, chemical-mechanical processes, CO2-assisted triaxial compression, steam permeation condensation (SPC), CO2 foaming in-situ conversion, and 3D and 4D printing technologies. However, it is rare to find foam materials that can simultaneously possess both "honeycomb" and "concave" cell morphologies in situ, except for 3D and 4D printing technologies. Therefore, it is even more difficult to locally control the cell morphology in situ. While 3D and 4D printing technologies enable the design and controllability of "honeycomb" and "concave" cell structures, their high-precision manufacturing processes are extremely slow, requiring significant energy and resources, resulting in low efficiency and high costs. More importantly, the cell sizes of polymer foam materials currently produced using 3D and 4D printing are relatively large, at the millimeter level, severely limiting their application in fields requiring lightweight materials and good mechanical properties. Therefore, there is an urgent need to develop a simple, green, efficient, and low-cost method to prepare lightweight, micron-sized polymer foam materials with excellent properties. This would greatly improve the usability of polymer foam materials and drive the development of this field. Summary of the Invention

[0004] In view of this, the purpose of the present invention is to provide a method for preparing polymer foam material with in-situ local control of cell morphology and a polymer foam material. The method can control the cell morphology in-situ during the preparation of polymer foam material, and the process is simple and environmentally friendly.

[0005] This invention provides a method for preparing polymer foam materials with in-situ localized control of cell morphology, comprising the following steps:

[0006] A foaming precursor is obtained by compounding polar polymers, non-polar polymers, hydrophilic substances, and additives; the hydrophilic substances account for 0-20 wt% and the additives account for 0-20 wt% in the foaming precursor.

[0007] The foaming precursor, foaming agent, and water are mixed and foamed at 60–200°C and 3–25 MPa for 30 min–8 h to obtain a polymer foam material.

[0008] Preferably, the polar polymer is selected from one or more of the following: polyvinyl chloride, chlorinated polyethylene, chlorinated polypropylene, organofluorine thermoplastic resin, organosilicon thermoplastic resin, thermoplastic polyurethane resin, thermoplastic polyurethane copolymer resin, polyamide resin, polyamide copolymer resin, polyester resin, polyester copolymer resin, poly(meth)acrylate polymer, poly(meth)acrylate copolymer, poly(meth)acrylate salt polymer, poly(meth)acrylate salt copolymer, ethylene-acrylate copolymer, ethylene-acrylate copolymer, ethylene-vinyl acetate copolymer, polyoxyethylene ether modified polypropylene, polyoxyethylene ether modified polyethylene, epoxy ethylene-styrene copolymer, epoxy propylene-styrene copolymer, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-styrene copolymer, and acrylonitrile-butadiene-styrene copolymer.

[0009] Preferably, the nonpolar polymer is selected from one or more of polyethylene, ethylene copolymer, polypropylene, propylene copolymer, polybutene, butene copolymer, polystyrene, polybutadiene, polyisoprene, olefin thermoplastic elastomers, and styrene thermoplastic polymers.

[0010] Preferably, the olefinic thermoplastic elastomer is selected from one or more of the following: ethylene propylene diene monomer (EPDM)-polypropylene thermoplastic vulcanizate, ethylene propylene diene monomer (EPDM)-polyethylene thermoplastic vulcanizate, natural rubber-polypropylene thermoplastic vulcanizate, natural rubber-polyethylene thermoplastic vulcanizate, isoprene-polypropylene thermoplastic vulcanizate, isoprene-polyethylene thermoplastic vulcanizate, polybutadiene rubber-polypropylene thermoplastic vulcanizate, and polybutadiene rubber-polyethylene thermoplastic vulcanizate.

[0011] The ethylene-based thermoplastic polymer is selected from one or more of styrene-butadiene block copolymers, styrene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, and styrene-ethylene / butene-styrene block copolymers.

[0012] Preferably, the mass ratio of the polar polymer to the non-polar polymer is (1:9) to (9:1).

[0013] Preferably, the hydrophilic material is selected from one or more of hydrophilic polymers, hydrophilic organic compounds, water-absorbing inorganic powders, and soluble inorganic salts;

[0014] The hydrophilic polymer is selected from one or more of the following: polyethylene glycol, ethylene-vinyl acetate copolymer, polypropylene glycol, polyvinyl acetate, polyacrylamide, poly(meth)acrylic acid, poly(meth)acrylate, poly(meth)acrylate, starch, cellulose, polypropylene-polyethylene glycol graft copolymer, polypropylene-polyethylene glycol block copolymer, polyethylene-polyvinyl alcohol graft copolymer, polyethylene-polyvinyl alcohol block copolymer, polystyrene-polyethylene glycol graft copolymer, and polystyrene-polyethylene glycol block copolymer.

[0015] The hydrophilic organic compound is selected from ethylene glycol, propylene glycol, glycerol, pentaerythritol, stearic acid, sodium stearate, potassium stearate, calcium stearate, zinc stearate, palmitic acid, sodium palmearate, potassium palmearate, calcium palmearate, zinc palmearate, adipic acid, sodium adipic acid, potassium adipic acid, calcium adipic acid, zinc adipic acid, succinic acid, sodium succinic acid, potassium succinic acid, calcium succinic acid, zinc succinic acid, sebacic acid, sodium sebacic acid, calcium sebacic acid, zinc sebacic acid, hexamethylenediamine, and octanediamine. Melamine, oleamide, erucamide, hexadecyltrimethylammonium bromide, dodecyl polyoxyethylene ether, tetradecyl polyoxyethylene ether, hexadecyl polyoxyethylene ether, octadecyl polyoxyethylene ether, alkylphenol polyoxyethylene ether, glyceryl palmitate, glyceryl stearate, Span series surfactants, Tween series surfactants, bromohexadecylpyridine, bromododecylpyridine, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, hexadecyl phosphate, octadecyl phosphate, or one or more of these;

[0016] The water-absorbing inorganic powder is selected from one or more of the following: expanded perlite, expanded vermiculite, sepiolite, montmorillonite, diatomaceous earth, attapulgite, bentonite, sepiolite, zeolite, and molecular sieve.

[0017] The soluble inorganic salt is selected from inorganic borates, inorganic carbonates, inorganic nitrates, inorganic phosphates, inorganic sulfates, inorganic chlorides, and inorganic bromides.

[0018] Preferably, the additive is selected from one or more of the following: calcium carbonate powder, talc powder, wollastonite powder, silica powder, alumina, aluminum hydroxide, magnesium oxide, zinc oxide, titanium dioxide, zirconium oxide, barium oxide, barium sulfate, activated carbon, carbon black, carbon nanotubes, carbon fiber, graphene, graphene oxide, manganese dioxide, iron oxide, nickel oxide, iron powder, iron fiber, copper powder, copper fiber, stainless steel powder, stainless steel fiber, nickel powder, nickel fiber, silver powder, silver fiber, gold powder, gold fiber, wood powder, bamboo powder, rice husk powder, and straw powder.

[0019] Preferably, the foaming agent is selected from one or more of CO2, N2, butane and pentane.

[0020] Preferably, the foaming process includes:

[0021] At 60–200℃ and 3–25MPa, after saturation for 30 min–8 h, the pressure is released to atmospheric pressure at a rate of 5–50 MPa / s.

[0022] This invention provides a polymer foam material prepared by the method described in the above technical solution.

[0023] This invention provides a method for in-situ localized control of the cell morphology of polymer foam materials, comprising the following steps: compounding a polar polymer, a non-polar polymer, a hydrophilic agent, and an additive to obtain a foaming precursor; the hydrophilic agent and the additive constitute 0-20 wt% of the foaming precursor; mixing the foaming precursor with a foaming agent and water, and foaming at 60-200℃ and 3-25 MPa for 30 min-8 h to obtain the polymer foam material. This method enables in-situ localized control of the cell morphology during the preparation of polymer foam materials, is simple, and environmentally friendly. It can control the morphology and Poisson's ratio of the polymer foam material, improving the designability of material properties, which will greatly enhance the usability of polymer foam materials and promote the development of this field. Attached Figure Description

[0024] Figure 1 This is a process flow diagram of the preparation method of the in-situ localized regulation of the cell morphology of polymer foam material according to the present invention.

[0025] Figure 2 Here is a SEM image of the polymer foam material prepared in Example 1 of this invention;

[0026] Figure 3 This is a SEM image of the polymer foam material prepared in Example 3 of the present invention. Detailed Implementation

[0027] This invention provides a method for preparing polymer foam materials with in-situ localized control of cell morphology, comprising the following steps:

[0028] A foaming precursor is obtained by compounding polar polymers, non-polar polymers, hydrophilic substances, and additives; the hydrophilic substances account for 0-20 wt% and the additives account for 0-20 wt% in the foaming precursor.

[0029] The foaming precursor, foaming agent, and water are mixed and foamed at 60–200°C and 3–25 MPa for 30 min–8 h to obtain a polymer foam material.

[0030] The method provided by this invention is a simple, green, efficient, and low-cost method capable of in-situ localized control of the cell morphology of polymer foam materials. This method for preparing polymer foam materials with in-situ localized control of cell morphology can regulate the morphology and Poisson's ratio of the polymer foam material, improving the designability of material properties. This will greatly enhance the usability of polymer foam materials and promote the development of this field.

[0031] Figure 1 This is a process flow diagram of the preparation method of the in-situ localized regulation of the cell morphology of polymer foam material according to the present invention.

[0032] This invention involves compounding polar polymers and non-polar polymers, hydrophilic substances, and additives to form a foaming precursor.

[0033] In this invention, the polar polymer is selected from one or more of the following: polyvinyl chloride, chlorinated polyethylene, chlorinated polypropylene, organofluorine thermoplastic resin, organosilicon thermoplastic resin, thermoplastic polyurethane resin, thermoplastic polyurethane copolymer resin, polyamide resin, polyamide copolymer resin, polyester resin, polyester copolymer resin, poly(meth)acrylate polymer, poly(meth)acrylate copolymer, poly(meth)acrylate salt polymer, poly(meth)acrylate salt copolymer, ethylene-acrylate copolymer, ethylene-acrylate copolymer, ethylene-vinyl acetate copolymer, polyoxyethylene ether modified polypropylene, polyoxyethylene ether modified polyethylene, epoxy ethylene-styrene copolymer, epoxy propylene-styrene copolymer, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-styrene copolymer, and acrylonitrile-butadiene-styrene copolymer.

[0034] In this invention, the nonpolar polymer is selected from one or more of polyethylene, ethylene copolymers, polypropylene, propylene copolymers, polybutene, butene copolymers, polystyrene, polybutadiene, polyisoprene, olefin thermoplastic elastomers, and styrene thermoplastic polymers. The olefin thermoplastic elastomers in this invention are selected from one or more of ethylene propylene diene monomer (EPDM) rubber-polypropylene thermoplastic vulcanizate, ethylene propylene diene monomer (EPDM) rubber-polyethylene thermoplastic vulcanizate, natural rubber-polypropylene thermoplastic vulcanizate, natural rubber-polyethylene thermoplastic vulcanizate, isoprene-polypropylene thermoplastic vulcanizate, isoprene-polyethylene thermoplastic vulcanizate, polybutadiene rubber-polypropylene thermoplastic vulcanizate, and polybutadiene rubber-polyethylene thermoplastic vulcanizate. The ethylene thermoplastic polymers are selected from one or more of styrene-butadiene block copolymers, styrene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, and styrene-ethylene / butene-styrene block copolymers.

[0035] In this invention, the mass ratio of the polar polymer to the non-polar polymer is (1:9) to (9:1); specifically, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 2:8, 8:2, 3:7, 7:3, 4:6, 6:4, or 5:5.

[0036] The foaming precursor prepared by this invention contains 0-20 wt% hydrophilic material and 0-20 wt% additives; the hydrophilic material is selected from one or more of hydrophilic polymers, hydrophilic organics, water-absorbing inorganic powders and soluble inorganic salts.

[0037] In specific embodiments, the mass ratio of polypropylene to thermoplastic polyurethane resin is 70:30; or the mass ratio of ethylene-octene copolymer, ethylene-vinyl acetate copolymer and talc is 10:80:5; or the mass ratio of polyamide copolymer resin and polystyrene is 80:20; or the mass ratio of polyethylene, ethylene-vinyl acetate copolymer and pentaerythritol is 60:34:6; or the mass ratio of polyisoprene, polyester resin and potassium octanoate is 60:40:10; or the mass ratio of polypropylene, polyamide copolymer resin and graphene oxide is 10:80:10.

[0038] More specifically, the polypropylene (PP) is model W531L, melting point 150℃, purchased from Suzhou Xinsuyu Plastic Raw Materials Co., Ltd.; the thermoplastic polyurethane resin (TPU) is model 6175AP, melting point 150℃, purchased from Guangzhou Dongcheng Chemical Co., Ltd.; and the ethylene-octene copolymer (POE) is model INFUSE. TM9100, melting point 120℃, purchased from Dow Chemical; Ethylene-vinyl acetate copolymer EVA, model: 18-3, melting point 99℃, purchased from Beijing Organic Chemical Plant; Polyamide copolymer resin PEBAX, model: 2533, melting point 140℃, purchased from Colette Trading Co., Ltd.; Polyamide copolymer resin PEBAX, model: 3533, melting point 160℃, purchased from Colette Trading Co., Ltd.; Polystyrene PS, model: GPPS, melting point 143℃, purchased from Shanghai Yisu Chemical Co., Ltd.; 1,4-trans-polyisoprene rubber, melting point 58℃, purchased from Wuhan Smike Biotechnology Co., Ltd.; Polycaprolactone, model: DG-C100, melting point 60℃, purchased from Jinan Daigang Bioengineering Co., Ltd.

[0039] The hydrophilic polymer is selected from one or more of the following: polyethylene glycol, ethylene-vinyl acetate copolymer, polypropylene glycol, polyvinyl acetate, polyacrylamide, poly(meth)acrylic acid, poly(meth)acrylate, poly(meth)acrylate, starch, cellulose, polypropylene-polyethylene glycol graft copolymer, polypropylene-polyethylene glycol block copolymer, polyethylene-polyvinyl alcohol graft copolymer, polyethylene-polyvinyl alcohol block copolymer, polystyrene-polyethylene glycol graft copolymer, and polystyrene-polyethylene glycol block copolymer.

[0040] The hydrophilic organic compound is selected from ethylene glycol, propylene glycol, glycerol, pentaerythritol, stearic acid, sodium stearate, potassium stearate, calcium stearate, zinc stearate, palmitic acid, sodium palmearate, potassium palmearate, calcium palmearate, zinc palmearate, adipic acid, sodium adipic acid, potassium adipic acid, calcium adipic acid, zinc adipic acid, succinic acid, sodium succinic acid, potassium succinic acid, calcium succinic acid, zinc succinic acid, sebacic acid, sodium sebacic acid, calcium sebacic acid, zinc sebacic acid, hexamethylenediamine, and octanediamine. Melamine, oleamide, erucamide, hexadecyltrimethylammonium bromide, dodecyl polyoxyethylene ether, tetradecyl polyoxyethylene ether, hexadecyl polyoxyethylene ether, octadecyl polyoxyethylene ether, alkylphenol polyoxyethylene ether, glyceryl palmitate, glyceryl stearate, Span series surfactants, Tween series surfactants, bromohexadecylpyridine, bromododecylpyridine, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, hexadecyl phosphate, and octadecyl phosphate;

[0041] The water-absorbing inorganic powder is selected from one or more of expanded perlite, expanded vermiculite, sepiolite, montmorillonite, diatomaceous earth, attapulgite, bentonite, sepiolite, zeolite, and molecular sieves.

[0042] The soluble inorganic salt is selected from borates, carbonates, nitrates, phosphates, sulfates, chlorides, and bromides of inorganic elements. The inorganic element in the soluble inorganic salt is selected from sodium, potassium, magnesium, calcium, aluminum, iron, copper, or zinc. Specifically, the soluble inorganic salt is selected from sodium borates, sodium carbonates, sodium nitrates, sodium phosphates, sodium sulfates, sodium chlorides, sodium bromides, potassium borates, potassium carbonates, potassium nitrates, potassium phosphates, potassium sulfates, potassium chlorides, potassium bromides, magnesium borates, magnesium carbonates, magnesium nitrates, magnesium phosphates, magnesium sulfates, magnesium chlorides, magnesium bromides, calcium borates, calcium carbonates, calcium nitrates, calcium phosphates, calcium sulfates, calcium chlorides, calcium bromides, aluminum borates, aluminum carbonates, aluminum nitrates, and aluminum... Phosphates, aluminum sulfates, aluminum chlorides, aluminum bromides, iron borates, iron carbonates, iron nitrates, iron phosphates, iron sulfates, iron chlorides, iron bromides, ferrous borates, ferrous carbonates, ferrous nitrates, ferrous phosphates, ferrous sulfates, ferrous chlorides, ferrous bromides, copper borates, copper carbonates, copper nitrates, copper phosphates, copper sulfates, copper chlorides, copper bromides, zinc borates, zinc carbonates, zinc nitrates, zinc phosphates, zinc sulfates, zinc chlorides, or zinc bromides.

[0043] The additives described in this invention are selected from one or more of the following: calcium carbonate powder, talc powder, wollastonite powder, silicon dioxide powder, alumina, aluminum hydroxide, magnesium oxide, aluminum hydroxide, zinc oxide, titanium dioxide, zirconium oxide, barium oxide, barium sulfate, activated carbon, carbon black, carbon nanotubes, carbon fiber, graphene, graphene oxide, manganese dioxide, iron oxide, nickel oxide, iron powder, iron fiber, copper powder, copper fiber, stainless steel powder, stainless steel fiber, nickel powder, nickel fiber, silver powder, silver fiber, gold powder, gold fiber, wood powder, bamboo powder, rice husk powder, and straw powder.

[0044] The preferred raw materials used in this invention include polypropylene and thermoplastic polyurethane resin in a mass ratio of 70:30; or ethylene-octene copolymer, ethylene-vinyl acetate copolymer and talc in a mass ratio of 10:85:5; or polyamide copolymer resin and polystyrene in a mass ratio of 80:20; or polyethylene, ethylene-vinyl acetate copolymer and pentaerythritol in a mass ratio of 60:34:6; or polyisoprene, polyester resin and potassium octanoate in a mass ratio of 60:40:10; or polypropylene, polyamide copolymer resin and graphene oxide in a mass ratio of 10:80:10.

[0045] The compounding and molding methods in this invention can be any methods well known to those skilled in the art, and there are no special limitations; the compounding method can be compounding by adding it to an internal mixer; or compounding by adding it to an extruder. The molding methods in this invention can be extrusion granulation, extrusion molding, calendering, compression molding, or injection molding. The composite material can be in granular form, or it can be made into any desired size and shape.

[0046] After obtaining the foaming precursor, the present invention mixes the foaming precursor with a foaming agent and water, and foams it at 60-200°C and 3-25 MPa for 30 min-8 h to obtain a polymer foam material.

[0047] The foaming equipment used in this invention is commonly used polymer foaming equipment, such as autoclave, molding, and box foaming equipment, but is not limited to these. Any equipment that can perform operations such as pressure holding, injection and permeation of foaming agent and water, and rapid pressure release to achieve polymer foaming can be used as the foaming equipment of this invention.

[0048] In this invention, the foaming temperature is 60–200°C, specifically 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, or 200°C. When the foaming temperature is below 60°C, the polymer system has a high viscosity, which is unfavorable for bubble nucleation and growth, resulting in poor foaming performance. Conversely, when the temperature is above 200°C, the polymer system has low melt strength, and the cells are prone to collapse and rupture.

[0049] In this invention, the foaming pressure is 3–25 MPa, specifically 3 MPa, 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa, 10 MPa, 11 MPa, 12 MPa, 13 MPa, 14 MPa, 15 MPa, 16 MPa, 17 MPa, 18 MPa, 19 MPa, 20 MPa, 21 MPa, 22 MPa, 23 MPa, 24 MPa, or 25 MPa. When the foaming pressure is below 3 MPa, the resulting polymer foam material has larger pores and lower mechanical strength; while when the pressure is above 25 MPa, the melt strength of the polymer system cannot withstand such high pressure, causing the resulting polymer foam material to rupture.

[0050] The foaming agent needs a certain amount of time to penetrate. If the penetration time is less than 30 minutes, the content of foaming agent and water will be too low, which will lead to a low foaming ratio and the inability to control the cell morphology locally. Considering the preparation efficiency and cell morphology control, the saturation time is 30 minutes to 8 hours. Specifically, it can be 30 minutes, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours.

[0051] In this invention, foaming refers to rapid depressurization; the foaming process includes: depressurizing after saturation for 30 minutes to 8 hours, depressurizing to atmospheric pressure, and depressurization rate of 5 to 50 MPa / s.

[0052] This invention opens the pressure relief valve of a foaming equipment to rapidly reduce the pressure inside the equipment from foaming pressure to atmospheric pressure, or to rapidly reduce the pressure to atmospheric pressure in several stages. The pressure relief rate is 5–50 MPa / s, specifically 5 MPa / s, 6 MPa / s, 7 MPa / s, 8 MPa / s, 9 MPa / s, 10 MPa / s, 11 MPa / s, 12 MPa / s, 13 MPa / s, 14 MPa / s, 15 MPa / s, 16 MPa / s, 17 MPa / s, 18 MPa / s, 19 MPa / s, 20 MPa / s, 21 MPa / s, 22 MPa / s, 23 MPa / s, 24 MPa / s, 25 MPa / s, and 26 MPa / s. , 27MPa / s, 28MPa / s, 29MPa / s, 30MPa / s, 31MPa / s, 32MPa / s, 33MPa / s, 34MPa / s, 35MPa / s, 36MPa / s, 37MPa / s, 38MPa / s , 39MPa / s, 40MPa / s, 41MPa / s, 42MPa / s, 43MPa / s, 44MPa / s, 45MPa / s, 46MPa / s, 47MPa / s, 48MPa / s, 49MPa / s or 50MPa / s.

[0053] During the foaming process, the foaming precursor of the present invention can be discharged outside the foaming equipment with the gas to complete the foaming and obtain polymer foam material, or it can be retained inside the foaming equipment to complete the foaming and then taken out to obtain polymer foam material.

[0054] This invention enables in-situ local control of the cell morphology of polymer foam materials by adjusting the ratio of polar and non-polar polymers, the content of added hydrophilic substances and additives, and the foaming conditions.

[0055] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0056] The present invention provides a method for in-situ localized control of cell morphology in polymer foam materials, which proposes a novel method for in-situ localized control of cell morphology during the preparation of polymer foam materials, thereby improving the controllability of polymer foam material preparation.

[0057] The method for preparing polymer foam material with in-situ localized control of cell morphology of the present invention has the characteristics of high production efficiency, low cost, small cell size of the prepared foam material, simple process, controllable process, green and environmentally friendly, and suitable for large-scale production.

[0058] The method for preparing polymer foam material with in-situ localized control of cell morphology of the present invention has low limitation on polymer type and polymer properties and has universality.

[0059] The in-situ localized control method for preparing polymer foam materials according to the present invention can control the morphology and Poisson's ratio of polymer foam materials, thereby improving the designability of material properties. This will greatly improve the usability of polymer foam materials and promote the development of this field.

[0060] The present invention also provides a polymer foam material, which is prepared by the preparation method described in the above technical solution.

[0061] The cell morphology of the polymer foam material provided by this invention includes one or both of the following: "honeycomb" and "concave corner" structures.

[0062] To further illustrate the present invention, the following detailed description, in conjunction with embodiments, of a method for preparing in-situ locally regulated polymer foam material and the polymer foam material provided by the present invention, should not be construed as limiting the scope of protection of the present invention.

[0063] Example 1

[0064] First, polypropylene (PP:W531L, melting point 150℃, Suzhou Xinsuyu Plastic Raw Materials Co., Ltd.) and thermoplastic polyurethane resin (TPU:6175AP, melting point 150℃, Guangzhou Dongcheng Chemical Co., Ltd.) were added to a twin-screw extruder at a mass ratio of 70:30. The mixing section temperature was 200℃, and the speed was 200 rpm. After extrusion and granulation, the mixture was then injection molded into a cubic composite material as a foaming precursor. The foaming precursor was then placed in a foaming device containing CO2 and water at 140℃ and 8MPa for 3 hours, after which the pressure was released to atmospheric pressure at a rate of 5MPa / s. During the depressurization foaming process, the foaming precursor was discharged from the foaming device with the gas, completing the foaming process and obtaining the foam material.

[0065] Testing revealed that the foam material exhibits numerous "honeycomb" cell morphologies and a small number of "concave" cell structures, as shown in the SEM images. Figure 2 As shown: the cell morphology within the elliptical circle is a "concave corner" structure, while the cell morphology within the square frame is a "honeycomb" structure; the Poisson's ratio of this material was tested according to GB / T1040.1-2006 standard, and the minimum Poisson's ratio value was 0.13.

[0066] Example 2

[0067] First, mix the ethylene-octene copolymer (POE:INFUSE) in a mass ratio of 10:85:5. TM9100 (melting point 120℃, Dow Chemical), ethylene-vinyl acetate copolymer (EVA:18-3, melting point 99℃, Beijing Organic Chemical Plant), and talc (Dongguan Jiran Powder Materials Co., Ltd.) were melt-mixed in an internal mixer for 10 minutes at a mixing temperature of 160℃ and a rotation speed of 100 rpm. While still hot, the mixture was placed in a spherical mold and pressed into a spherical composite material as a foaming precursor. The foaming precursor was then placed in a foaming device at 130℃ and 12MPa of N2 and water for 4 hours, after which the pressure was released to atmospheric pressure at a rate of 10MPa / s. During the depressurization foaming process, the foaming precursor remained inside the foaming device to complete foaming. The foaming device was then opened and the precursor was removed to obtain the foam material.

[0068] Testing revealed that the foam material exhibited a honeycomb-like cell structure. The Poisson's ratio was tested according to GB / T1040.1-2006 standard, with a minimum Poisson's ratio of 0.28.

[0069] Example 3

[0070] First, polyamide copolymer resin (PEBAX:2533, melting point 140℃, Colette Trading Co., Ltd.) and polystyrene (PS:GPPS, melting point 143℃, Shanghai Yisu Chemical Co., Ltd.) were added to a Banbury mixer at a mass ratio of 80:20 and mixed for 8 minutes at a mixing temperature of 150℃ and a rotation speed of 100 rpm. The mixture was then placed in a square mold and pressed into a square composite material as a foaming precursor. The foaming precursor was then placed in a foaming device containing CO2 and water at 130℃ and 12 MPa for 6 hours, after which the pressure was released to atmospheric pressure at a rate of 6 MPa / s. During the depressurization foaming process, the foaming precursor remained inside the foaming device to complete foaming. The foaming device was then opened and the precursor was removed to obtain the foam material.

[0071] Testing revealed that the foam material exhibited a concave pore structure, as shown in the SEM images. Figure 3 As shown. The Poisson's ratio of this foam material was tested according to GB / T1040.1-2006 standard, and the minimum Poisson's ratio was -0.31.

[0072] Example 4

[0073] First, polyethylene (PE:1806H, melting point 112℃, LyondellBasell), ethylene-vinyl acetate copolymer (EVA:18-3, melting point 99℃, Beijing Organic Chemical Plant), and pentaerythritol (Bailingwei Technology Co., Ltd.) were added to a twin-screw extruder at a mass ratio of 60:34:6. The mixing section temperature was 200℃, and the mixture was extruded and granulated. The resulting sheet-like composite material was then used as a foaming precursor by injection molding. Next, the foaming precursor was placed in a foaming device containing CO2, pentane, and water at 120℃ and 15MPa for 3 hours. The pressure was then released to atmospheric pressure at a rate of 10MPa / s. During the depressurization foaming process, the foaming precursor remained inside the foaming device to complete foaming. Afterward, the foaming device was opened, and the precursor was removed to obtain the foam material.

[0074] Testing revealed that a small number of cells with a concave pore structure were interspersed among cells with a honeycomb structure in the foam material. The Poisson's ratio of the material was tested according to GB / T1040.1-2006 standard, and the minimum Poisson's ratio was 0.06.

[0075] Example 5

[0076] First, polyisoprene (1,4-trans-polyisoprene rubber, melting point 58℃, Wuhan Smike Biotechnology Co., Ltd.), polyester resin (polycaprolactone: DG-C100, melting point 60℃, Jinan Daigang Bioengineering Co., Ltd.), and potassium octanoate (Hubei Xinrunde Chemical Co., Ltd.) were added to a single-screw extruder at a mass ratio of 60:40:10. The mixing section temperature was 150℃, and the mixture was extruded and granulated. The resulting square composite material was then injection molded as a foaming precursor. Next, the foaming precursor was placed in a foaming device at 110℃ and 9MPa N2 and water for 2 hours, after which the pressure was released to atmospheric pressure at a rate of 5MPa / s. During the depressurization foaming process, the foaming precursor remained inside the foaming device to complete foaming. The foaming device was then opened, and the precursor was removed to obtain the foam material.

[0077] Testing revealed that the foam material exhibited a honeycomb-like cell structure. The Poisson's ratio was tested according to GB / T1040.1-2006 standard, with a minimum Poisson's ratio of 0.16.

[0078] Example 6

[0079] First, polypropylene (PP:W531L, melting point 150℃, Suzhou Xinsuyu Plastic Raw Materials Co., Ltd.), polyamide copolymer resin (PEBAX:3533, melting point 160℃, Kolette Trading Co., Ltd.), and graphene oxide (Hangzhou Gaoxi Technology Co., Ltd.) were added to a mixer at a mass ratio of 10:80:10 and mixed for 8 minutes at a mixing temperature of 180℃ and a rotation speed of 100 rpm. Then, the mixture was placed in a circular mold and pressed into a circular composite material as a foaming precursor. Next, the foaming precursor was placed in a foaming device containing CO2 and water at 135℃ and 12MPa for 4 hours, after which the pressure was released to atmospheric pressure at a rate of 5MPa / s. During the depressurization foaming process, the foaming precursor remained inside the foaming device to complete foaming. Afterward, the foaming device was opened and the precursor was removed to obtain the foam material.

[0080] Testing revealed that the foam material has a large number of "concave" pore structures and a small number of "honeycomb" pore structures; the Poisson's ratio of the material was tested according to GB / T1040.1-2006 standard, and the minimum Poisson's ratio value was -0.19.

[0081] As can be seen from the above embodiments, the present invention provides a method for preparing polymer foam materials with in-situ localized control of cell morphology, comprising the following steps: compounding a polar polymer and a non-polar polymer, a hydrophilic agent, and an additive to obtain a foaming precursor; the hydrophilic agent accounts for 0-20 wt% and the additive accounts for 0-20 wt% in the foaming precursor; mixing the foaming precursor with a foaming agent and water, and foaming at 60-200℃ and 3-25 MPa for 30 min-8 h to obtain the polymer foam material. This method can control the cell morphology in-situ during the preparation of polymer foam materials, is simple, and environmentally friendly; this method can control the morphology and Poisson's ratio of polymer foam materials, improving the designability of material properties, which will greatly improve the usability of polymer foam materials and promote the development of this field.

[0082] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing polymer foam material with in-situ localized control of cell morphology, comprising the following steps: A foaming precursor is obtained by compounding polar polymers, non-polar polymers, hydrophilic substances, and additives; the hydrophilic substances account for 0-20 wt% and the additives account for 0-20 wt% in the foaming precursor. The foaming precursor, foaming agent, and water are mixed and foamed at 60–200°C and 3–25 MPa for 30 min–8 h to obtain a polymer foam material.

2. The preparation method according to claim 1, characterized in that, The polar polymer is selected from one or more of the following: polyvinyl chloride, chlorinated polyethylene, chlorinated polypropylene, organofluorine thermoplastic resins, organosilicon thermoplastic resins, thermoplastic polyurethane resins, thermoplastic polyurethane copolymers, polyamide resins, polyamide copolymers, polyester resins, polyester copolymers, poly(meth)acrylate polymers, poly(meth)acrylate copolymers, poly(meth)acrylate salt polymers, poly(meth)acrylate salt copolymers, ethylene-acrylate copolymers, ethylene-acrylate copolymers, ethylene-vinyl acetate copolymers, polyoxyethylene ether modified polypropylene, polyoxyethylene ether modified polyethylene, ethylene oxide-styrene copolymers, propylene oxide-styrene copolymers, acrylonitrile-butadiene-styrene copolymers, acrylonitrile-styrene copolymers, and acrylonitrile-butadiene-styrene copolymers.

3. The preparation method according to claim 1, characterized in that, The nonpolar polymer is selected from one or more of polyethylene, ethylene copolymer, polypropylene, propylene copolymer, polybutene, butene copolymer, polystyrene, polybutadiene, polyisoprene, olefin thermoplastic elastomers, and styrene thermoplastic polymers.

4. The preparation method according to claim 3, characterized in that, The olefin-based thermoplastic elastomer is selected from one or more of the following: ethylene propylene diene monomer (EPDM)-polypropylene thermoplastic vulcanizate, ethylene propylene diene monomer (EPDM)-polyethylene thermoplastic vulcanizate, natural rubber-polypropylene thermoplastic vulcanizate, natural rubber-polyethylene thermoplastic vulcanizate, isoprene-polypropylene thermoplastic vulcanizate, isoprene-polyethylene thermoplastic vulcanizate, polybutadiene rubber-polypropylene thermoplastic vulcanizate, and polybutadiene rubber-polyethylene thermoplastic vulcanizate. The ethylene-based thermoplastic polymer is selected from one or more of styrene-butadiene block copolymers, styrene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, and styrene-ethylene / butene-styrene block copolymers.

5. The preparation method according to claim 1, characterized in that, The mass ratio of the polar polymer to the non-polar polymer is (1:9) to (9:1).

6. The preparation method according to claim 1, characterized in that, The hydrophilic material is selected from one or more of hydrophilic polymers, hydrophilic organic substances, water-absorbing inorganic powders, and soluble inorganic salts; The hydrophilic polymer is selected from one or more of the following: polyethylene glycol, ethylene-vinyl acetate copolymer, polypropylene glycol, polyvinyl acetate, polyacrylamide, poly(meth)acrylic acid, poly(meth)acrylate, poly(meth)acrylate, starch, cellulose, polypropylene-polyethylene glycol graft copolymer, polypropylene-polyethylene glycol block copolymer, polyethylene-polyvinyl alcohol graft copolymer, polyethylene-polyvinyl alcohol block copolymer, polystyrene-polyethylene glycol graft copolymer, and polystyrene-polyethylene glycol block copolymer. The hydrophilic organic compound is selected from ethylene glycol, propylene glycol, glycerol, pentaerythritol, stearic acid, sodium stearate, potassium stearate, calcium stearate, zinc stearate, palmitic acid, sodium palmearate, potassium palmearate, calcium palmearate, zinc palmearate, adipic acid, sodium adipic acid, potassium adipic acid, calcium adipic acid, zinc adipic acid, succinic acid, sodium succinic acid, potassium succinic acid, calcium succinic acid, zinc succinic acid, sebacic acid, sodium sebacic acid, calcium sebacic acid, zinc sebacic acid, hexamethylenediamine, and octanediamine. Melamine, oleamide, erucamide, hexadecyltrimethylammonium bromide, dodecyl polyoxyethylene ether, tetradecyl polyoxyethylene ether, hexadecyl polyoxyethylene ether, octadecyl polyoxyethylene ether, alkylphenol polyoxyethylene ether, glyceryl palmitate, glyceryl stearate, Span series surfactants, Tween series surfactants, bromohexadecylpyridine, bromododecylpyridine, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, hexadecyl phosphate, and octadecyl phosphate; The water-absorbing inorganic powder is selected from one or more of the following: expanded perlite, expanded vermiculite, sepiolite, montmorillonite, diatomaceous earth, attapulgite, bentonite, sepiolite, zeolite, and molecular sieve. The soluble inorganic salt is selected from inorganic borates, inorganic carbonates, inorganic nitrates, inorganic phosphates, inorganic sulfates, inorganic chlorides, and inorganic bromides.

7. The preparation method according to claim 1, characterized in that, The additives are selected from one or more of the following: calcium carbonate powder, talc powder, wollastonite powder, silicon dioxide powder, alumina, aluminum hydroxide, magnesium oxide, aluminum hydroxide, zinc oxide, titanium dioxide, zirconium oxide, barium oxide, barium sulfate, activated carbon, carbon black, carbon nanotubes, carbon fiber, graphene, graphene oxide, manganese dioxide, iron oxide, nickel oxide, iron powder, iron fiber, copper powder, copper fiber, stainless steel powder, stainless steel fiber, nickel powder, nickel fiber, silver powder, silver fiber, gold powder, gold fiber, wood powder, bamboo powder, rice husk powder, and straw powder.

8. The preparation method according to claim 1, characterized in that, The foaming agent is selected from one or more of CO2, N2, butane and pentane.

9. The preparation method according to claim 1, characterized in that, The foaming process includes: At 60–200℃ and 3–25MPa, after saturation for 30 min–8 h, the pressure is released to atmospheric pressure at a rate of 5–50 MPa / s.

10. A polymer foam material, prepared by the preparation method according to any one of claims 1 to 9.